What Is the Assembly Pathway of a Conjugated Polymer From Solution to Thin Films? - Xu, Zhuang; Park, Kyung Sun; Diao, Ying (Frontiers in Chemistry, 2020)
The hierarchical assembly of conjugated polymers has gained much attention due to its critical role in determining the optical/electrical/mechanical properties. The hierarchical morphology encompasses molecular scale intramolecular conformation (torsion angle, chain folds) and intermolecular ordering (π-π stacking), mesoscale domain size, orientation and connectivity, and macroscale alignment and (para)crystallinity. Such complex morphology in the solid state is fully determined by the polymer assembly pathway in the solution state, which in turn is sensitively modulated by molecular structure and processing conditions. However, molecular pictures of polymer assembly pathways remain elusive, due to the lack of detailed structural characterizations in the solution state and lack of understanding on how various factors impact the assembly pathways. In this mini review, we present possible assembly pathways of conjugated polymers and their characteristics across length scales. Recent advances in understanding and controlling of assembly pathways are highlighted. We also discuss the current gap in our knowledge of assembly pathways, with future perspectives on research needed on this topic.